Penggunaan Hasil Fermentasi Bungkil Kedelai Dalam Ransum Terhadap Pertumbuhan Ayam Pedaging - Al Qudri (Agricultural Faculty, 2001)
ABSTRACT. Tempe of soybean is fermented soybean with Rhizopus ologosporus fungus. From a result of researchers, it is the fact that tempe can increase valuable of nutrion and digest capacity and also produce antibiotic . Utilization of abtibiotic in chiken food as stimulus growth in not recommended because it can cause resistance a certain germ and it is presume there are antibiotic residu in egg and chiken meat. It is hope that the use of fermented soybean oil meal can increase nutrient value and digest capacity as well as produce antibiotic, so that it can get a better growth and over come a problem of using antibiotic in chiken food. The study was conducted to evaluate the effect of fermented soybean oil meal utilization in the ration on body weight gain, feed consumption, feed conversion and mortality. The study use 80 unsex day old chick broiler CP-707 and conducted at Poulty Laboratory Product Agriculture Faculty, Syiah Kuala University. Chiken were putting in 27 houses unit, each unit contain of four chiken. The design of experiment was Completely Randomized Design, four treatments and five replication. The treatments were ration contained 0%, 5%, 10% and 15% fermented soybean oil meal as replace the use of soybean oil meal. The protein and energy content of all dietary treatments were equally composed from six weeks investigation, were body weight gain, feed consumption, feed conversion and mortality. The result of the study indicated that up to 10% graded of fermented soybean oil meal in ration were significant difference influenced increase the body weight gain and decrease the feed conversion. The fermented soybeanoil meal) utilization more than 10% were significant difference decrease the body weight gain and increase the feed conversion. If the inclusion was increase the feed consumption would tendency decline. In this study there were no mortality in all treatment. In can be advised from this study that fermented soybean oil meal could be used in broiler ration or in all poulty ration.